Vascular Neurologists' Involvement in the Care of Medicare Patients With Ischemic Stroke. (July 2020) - Sacchetti, Daniel C.; Gupta, Ajay; Chung, Caroline D.; Chatterjee, Abhinaba; Zhang, Yi; Navi, Babak B.; Segal, Alan Z.; Kamel, Hooman
Background and Purpose: We sought to determine the proportion of patients with ischemic stroke evaluated by vascular neurologists in the United States. Methods: Using 2009 to 2015 claims from a 5% nationally representative sample of Medicare beneficiaries, we identified patients ≥65 years of age who were hospitalized for ischemic stroke. We ascertained the proportion of patients evaluated during the hospitalization or within 90 days of discharge by nonvascular and vascular neurologists. We assessed the relationship between county-level socioeconomic status and the likelihood of neurologist evaluation and between neurologist evaluation and diagnostic testing. Results: Among 66 989 patients with ischemic stroke, 37 820 (56.5%) were evaluated by a nonvascular neurologist and 11 700 (17.5%) by a board-certified vascular neurologist. Across increasing quartiles of county socioeconomic advantage, the proportion of patients evaluated by a vascular neurologist was 12.2%, 16.5%, 19.8%, and 23.0%. Relative to evaluation by a nonvascular neurologist, evaluation by a vascular neurologist was associated with a higher likelihood of postdischarge heart rhythm monitoring (odds ratio [OR], 1.8; 95% confidence interval [CI], 1.6-1.9), echocardiography (OR, 1.4; 95% CI, 1.3-1.4), cervical vessel imaging (OR, 1.3; 95% CI, 1.2-1.3), and intracranial vessel imaging (OR, 2.1; 95% CI, 2.0-2.2). Conclusions: In a nationally representative cohort of Medicare beneficiaries, we found that about three quarters of patients with ischemic stroke were evaluated by a neurologist, and about one-sixth were evaluated by a vascular neurologist. Patients who were evaluated by a vascular neurologist were significantly more likely to undergo diagnostic testing.